GEOTEXTILE IN THE MODERN INTERIOR: FEATURES OF USE IN THE DESIGN OF A PHYTOMODULE FOR GREEN WALL - OLIJNYK, Halina (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of research related to the features of using a geotextile material – geotextile profile membrane Izolit Green in the design of a phytomodule for vertical greening of a modern interior. The phytomodule is a modern trend, a unique design; clean indoor air and easy maintenance; it’s coziness and comfort. Vertical landscaping with the help of a phytomodule will advantageously distinguish the room, create the appropriate mood and give it a special charm. Phytomodules for landscaping are a modern solution for decorating a living space. A picture, a wall or a movable structure – everyone can find their own option based on the stylistic preferences and features of the design of the apartment or house. Vertical gardening is a great alternative to nature, requires a minimum of space, and the wall will look different. Phytowall can be easily placed near the desk in the office or apartment. Vertical gardening is a piece of nature that we need, which gives us strength and inspiration. Vertical landscaping is, without exaggeration, one of the most popular and universal trends in interior design. A green wall will help save space for placing plants, create the effect of a natural environment, clean the air and increase humidity in the room. The phytosystem consists of a phytomodule in which live indoor plants are planted. The modular design allows you to assemble green walls of any size.Correctly selected geotextile material can increase the reliability of the phytomodule, increase the time between repair and maintenance work, and extend the life of the phytomodule. Geotextile materials used in the construction of the phytomodule must ensure high-quality drainage properties and rigidity of the structure itself. The varieties of phytomodules, their advantages and disadvantages, features of filling are considered. The structure of the phytomodule was studied, an important component of which is geotextile, which ensures the qualitative characteristics of the phytomodule, in particular, the effective removal of excess moisture and the strength of the structure. The technical characteristics of the geotextile profiled membrane Izolit Green, which can be used in the design of the phytomodule, are considered. The assortment of ideas for garden walls based on the phytomodule is considered.
Keywords: geotextile materials; phytomodule; constructive; geosynthetic materials; profiled membrane; construction; stiffness; phytosystem